Effectiveness of Consumption of Moringa Leaves, Fe Tablets with Dates and Fe Tablets Against Increasing Hemoglobin in Pregnant Women with Anemia - Kahirah, Rahayu; Nurdiana; Nashrillah, Mulya Pahlawati; Royani, Irma; Susanti, Rozanila; Riance, Weni; Lasmita, Witri; Karmilah (Jurnal Penelitian Pendidikan IPA, 2024)
Anemia is a significant health issue with serious consequences, including increased maternal and infant mortality and reduced performance in various activities. In pregnant women, nutritional anemia not only jeopardizes the mother's health but also affects fetal development and pregnancy outcomes. This study aimed to assess the effectiveness of consuming Moringa leaves and dates in increasing hemoglobin levels in pregnant women with anemia. A quasi-experimental design with a pre-test and post-test was used, involving 210 pregnant women divided into two groups. Group 1 received Moringa leaves and Fe tablets, while Group 2 received dates and Fe tablets, with interventions lasting 30 days. Initial tests showed moderate anemia in both groups. After the intervention, significant improvements in hemoglobin levels were observed in both groups. However, the combination of dates and Fe tablets proved more effective than Moringa leaves and Fe in raising hemoglobin levels. The findings suggest that both Moringa leaves and dates are effective in combating anemia in pregnant women, with dates showing slightly better results.